Multilateral Development Banks Governance and Finance - Delikanli, Ihsan Ugur (Springer International Publishing, 2018)
"This book provides much needed insights and knowledge about the growing world of multilateral development banks. By including twenty-five global, regional, and sub-regional banks, it systematically presents main features, challenges, and potentials of these important development institutions. The book should be mandatory reading by everyone dealing with MDBs-both from the inside and from the outside." -Per Øyvind Bastøe, Evaluation Director, Norad; Chair of OECD/DAC EvalNet; former MDB senior official and board member "Multilateral Development Banks: Governance and Finance is a must read for those seeking increased knowledge and understanding of the complex world of multilateral development banks. The authors provide a service by not treating the MDBs as a unitary concept, but rather covering them as a family, and then discussing them by groupings based on their geographic lending outreach. But perhaps most interesting and certainly thought-provoking is the authors' proposed vision for boosting complementarities and effectiveness across the MDBs-suggestions and recommendations that are bound to set the debate for years to come." -Dr. Linda Morra Imas, Co-Director, author, and lead instructor, IPDET (International Program for Development Evaluation Training) 1.0; former advisor and chief evaluation officer at the World Bank and IFC; consultant to the World Bank, UN, and bilateral aid agencies and foreign ministries This book provides a comprehensive overview and insight of virtually all multilateral institutions involved in lending for international socio-economic development. The analysis covers twenty-five MDBs globally by classifying them in three groups based on geographical lending outreach. Unlike similar books and articles, which treat MDBs as banks, this book offers a novel perspective by addressing the specifics of multilateral lending institutions, revealing multiple aspects of their operations, going beyond the "bank" concept towards "knowledge bank," "change agent," and even "benchmark setter." The book reflects on the key role of most MDBs in inspiring and advancing sustainable economic development though transfer of knowledge and funding towards addressing multiple global challenges for the benefit of practitioners, consultants, government officials, borrowers, and researchers interested in MDBs. .